Maternal–fetal death in medieval Pieve di Pava (central Italy, 10th–12th century AD). (15th April 2021) - Riccomi, Giulia; Felici, Cristina; Giuffra, Valentina
Abstract: Despite the assumed elevated rates of young female mortality in ancient times, likely associated with pregnancy and childbirth risks, evidence of maternal–fetal deaths is surprisingly scarce in the osteoarchaeological record. Archaeological excavations conducted in the medieval rural cemetery of Pieve di Pava (Tuscany, central Italy) brought to light the burials of four young females deceased with fetuses. This research aims to reconstruct the osteobiographies of these mothers and the unborn children in order to investigate potential complications that may have played a role in their death. In this context, a paleopathological analysis of the female individuals was performed along with the examination of fetal position and the assessment of gestational age (GA) to explore potential links to obstetrical deaths. The spatial association of the mother and the fetus suggests a death during the later stages of pregnancy or childbirth for the two individuals T. 71 and US 8432; moreover, the position of her preterm 8‐month fetus, found between her legs of the latter, might be consistent with a case of postmortem fetal extrusion, a phenomenon that is rarely observed in osteoarchaeology. According to the same analytical criteria, two other females (T. 99 and US 8941), with an eight/nine‐month and a six‐month fetus respectively, reasonably died during pregnancy. The study of these cases from medieval Italy contributes to current interpretations of maternal–fetal death in the past, providing insights into the health status of young females and the risks they may have faced during pregnancy and childbirth.